Role of Women in Dairy Farming - Lahoti, S R; R, Chole S; S, Rathi N (Indian Journal of Dairy Science, 2012)
The present study was conducted to know the role of women dairy husbandry practices in Beed district of Maharashtra State. A simple random sampling technique was used in the selection of dairy farm women. The total sample constitutes 150 dairy farm women, 10 from 15 randomly selected villages of Ambajogai Tahsil. The selected respondents were interviewed personally with the help of a pre tested and well structured interview schedule to elicit information. They were actively involved in various aspects of dairy farming activities like care of new born calf, cleaning of animal shed, cleaning of utensils, storage of concentrates, feeding young calf, diagnosis of common disease and care at home level, care of sick animals, watering the live stock, offering the concentrate mixture, soaking the concentrate mixture, care during pregnancy, disposal of infected litter materials, grooming, cleaning and bathing buffaloes and cows. It is also observed that the participation of women was less in enrichment of dry fodder, money transaction like involvement in banking process, purchasing and sell of animals, maintenance of account financial records, maintenance of farm records, involvement in dairy co operatives and purchasing of equipments .